Efficiency Investigation of Metallized Film Capacitor Electrodes Segmentation Patterns - Ivanov I.O.; Belko V.O.; Glivenko D.Y.; Feklistov E.G.; Kulbako K.A. (Problems of the Regional Energetics, 2020)
The results of theoretical efficiency investigation of metallized film capacitor electrodes segmen-tation patterns are presented in this article. The aim of present investigation was the most effec-tive patterns configuration determination using by numerical simulation method. The experi-mental investigation method of metallized film capacitor electrodes electrodynamic destruction was developed to reach the needed scope. This method differs from the known methods by us-ing samples of metallized polymer film with different segmentation patterns instead of real ca-pacitors. Based on experimental results the numerical model of segmented electrodes electrody-namic destruction was developed using by COMSOL Multiphysics software. This numerical model allows to investigate different segmentation pattern’s efficiency during self-healing pro-cess (recovery of operating ability after dielectric breakdown) and to determine metallization’s electrical parameters without experimental investigations. Existing and novel types of segmented electrodes for metallized film capacitors were investigated. The dependence of electrodynamic destruction energy, i.e. energy needed to breakdown channel isolating, versus destruction time was used as a criterion of segmentation pattern efficiency. Advantages and disadvantages of in-vestigated electrodes segmentation types were determined. The most important result is the best pattern configuration determination. It was found that bridge-diamond segmentation is the most effective patterns configuration for metallized film capacitor’s application. The significance of the obtained results is practical application in capacitor’s manufacturing ability. The developed numerical model and investigation results can be used in design of new metallized film capaci-tors types with high specific characteristics.